An enigmatic new species of Belostoma Latreille from central-western Brazil (Heteroptera: Belostomatidae: Belostomatini) - Stefanello, Fabiano; Rodrigues, Higor D. D. (Zootaxa, 2021)
The new species Belostoma inusitatum is described and illustrated based on specimens from the west side of the Araguaia-Tocantins basin, in Mato Grosso state in central-western Brazil. This new species is assigned to the B. triangulum species group and compared with its congeners. A key and distribution map for the species of this group are included. The three-articulated antenna without lateral projections of B. inusitatum n. sp. is documented for the first time in Belostoma. Also, the uncommon shape of the prosternal keel, the distinct reduction of the hemelytral membrane, and the diverticulum of the phallosoma sharply incised at the posterior margin are reported for this new species. A discussion about the reduction in the number of antennal articles and the size of the hemelytral membrane in Belostoma and Abedus is presented.